Impact of polyvinyl alcohol fiber on the full life-cycle shrinkage of cementitious composite. (1st January 2023) - Wang, Qing; Xiong, Zihao; Zhang, Jun; Fang, Zhaosong; Lai, Mianheng; Ho, Johnny
Abstract: Engineered cementitious composite (ECC) enjoys huge potential in building structures thanks to its excellent tensile performance and energy absorption ability. However, free deformation of ECC deserves better understanding since large shrinkage strain usually induces internal tensile stress which would lead to cracking under constraint. Present study focuses on the full life-cycle shrinkage of polyvinyl alcohol (PVA) fiber reinforced ECC. Shrinkage and relative humidity (RH) at three water to cement (w/c) ratios were experimentally tested through novel integrated deformation measurement device. In contrast, plain mortars with the same w/c ratios were compared to evaluate the impact of PVA fiber on the over-time deformation and RH characteristics. Thereafter, shrinkage model considering fiber influence coefficient is established to simulate autogenous and drying shrinkage of PVA-ECC. Results show that full life-cycle shrinkage can be divided into two stages according to the internal RH measured. Distinct restraint effect of PVA fiber on both stages are observed. By comparing experimental and simulation results of PVA-ECC, the proposed fiber influence coefficient-based shrinkage model well illustrates the effect of PVA fiber, especially for high strength cementitious composites with relatively low w/c. Highlights: Full life-cycle shrinkage of mortar and PVA-ECC was innovatively evaluated. Restraint effect of PVA fiber on shrinkage is distinct for composites with various w/c ratios. Shrinkage model is established based on fiber influence coefficient. Proposed model well describes the full life-cycle shrinkage of PVA-ECC, especially for high strength composites.